德州市与山东省区际间经济发展差距研究 = A study on the regional differences in economic development in Shandong province and its implications to Dezhou city - 隋力 Sui, Li (2008)
This thesis is an empirical study on the differences in economic development among the three main regions in Shandong Province of China. In particular, we will explore the possible implications to the economic development to Dezhou City, a relatively less developed area in the western region of Shandong province. By using the coefficient of variation (C V) as a measure of development difference, we will analyze the differences in the output indicator, represented by GDP per capita, and livelihood indicators, such as urban average income, rural average income, among 17 municipal districts and among three main regions for the period of 1978 to 1998. We then use a ratio measure to benchmark the economic development performance of Dezhou City against the three regions. From these analyses, we will highlight the key trend and the main causes for the development gap between the Dezhou City and the eastern and the central regions.